PENGARUH BRAND IMAGE DAN PERSONAL BRANDING “FELICYA ANGELISTA” TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING DI KOTA MEDAN - Sianipar, Gloria J.M; Sinaga, Juliasti Viktoria (Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine the effect of brand image and personal branding "Felicya Angelista" on purchasing decisions in the city of Medan. This research is a research with a quantitative approach. The sample in this study were users of the Scarlett Whitening product in the city of Medan totaling 100 respondents with the sampling technique using purposive sampling technique. From the t-test results, the brand image variable has a positive and significant effect on purchasing decisions and the personal branding variable has a positive and significant effect on purchasing decisions. Based on the results of the F test, brand image and personal branding variables simultaneously have a positive and significant effect on purchasing decisions. In this study, the coefficient of determination (R2) was 30.3%, which indicates brand image (X1) and personal branding (X2) on purchasing decisions (Y), the remaining 69.7% influenced by variables not examined.